Impact of a digital health intervention on asthma resource utilization - Rajan Merchant; Stanley J. Szefler; Bruce G. Bender; Michael Tuffli; Meredith A. Barrett; Rahul Gondalia; Leanne Kaye; David Van Sickle; David A. Stempel (World Allergy Organization Journal, 2018)
Abstract Digital health interventions have been associated with reduced rescue inhaler use and improved controller medication adherence. This quality improvement project assessed the benefit of these interventions on asthma-related healthcare utilizations, including hospitalizations, emergency department (ED) utilization and outpatient visits. The intervention consisted of electronic medication monitors (EMMs) that tracked rescue and controller inhaler medication use, and a digital health platform that presented medication use information and asthma control status to patients and providers. In 224 study patients, the number of asthma-related ED visits and combined ED and hospitalization events 365 days pre- to 365 days post-enrollment to the intervention significantly decreased from 11.6 to 5.4 visits (p < 0.05) and 13.4 to 5.8 events (p < 0.05) per 100 patient-years, respectively. This digital health intervention was successfully incorporated into routine clinical practice and was associated with lower rates of asthma-related hospitalizations and ED visits.